2001
DOI: 10.1108/09578230110392884
|View full text |Cite
|
Sign up to set email alerts
|

“I don’t have enough time” ‐ Teachers’ interpretations of time as a key to learning and school change

Abstract: Time is one of the greatest constraints to any change process. However, finding more time for teachers by reallocating time within a fixed schedule has not brought about desired reforms. This article, based on a qualitative study that explored teachers’ interpretations of time, indicates that the concept of time is more complex and dynamic than the literature implies. It elaborates and illustrates nine aspects of time that teachers in a middle school instructional technology project identified as barriers to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 6 publications
2
42
0
2
Order By: Relevance
“…For example, teachers report that sustained and intensive professional development has a greater effect on changing practice than shorter professional development (Collinson and Cook 2001;Day and Leith 2007;Garet et al 2001). Professional development is more likely to be effective in improving teachers' knowledge and skills if it forms a coherent programme of teacher learning (Day and Leith 2007;Garet et al 2001;Loxley et al 2007).…”
Section: Influences On Teacher Professional Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, teachers report that sustained and intensive professional development has a greater effect on changing practice than shorter professional development (Collinson and Cook 2001;Day and Leith 2007;Garet et al 2001). Professional development is more likely to be effective in improving teachers' knowledge and skills if it forms a coherent programme of teacher learning (Day and Leith 2007;Garet et al 2001;Loxley et al 2007).…”
Section: Influences On Teacher Professional Developmentmentioning
confidence: 99%
“…Teachers often select the professional development in which they will participate from a number of options available from a highly disparate set of providers (Collinson and Cook 2001;Day and Leith 2007;Harris et al 2006;OECD 2009). Compounding this is the evidence that suggests that teachers' knowledge, beliefs, and attitudes impact how and what they learn from these professional development activities (Spillane and Thompson 1997).…”
Section: Influences On Teacher Professional Developmentmentioning
confidence: 99%
“…Previous studies identified many institutional and personal barriers in the process of multicultural teacher education (for example, Collinson & Cook, 2000;Fuller, 1992;Wang, 2008). The significant relationship between preservice teacher's attribution and cultural competence suggests that when preservice teachers feel they are in charge, they will be more likely to act as agents of change and practice culturally responsive pedagogy.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers report that professional development that involves sustained and intensive professional learning has a greater effect on changing practice than shorter, isolated professional learning 'events' such as one-stop workshops (Collinson and Cook 2001;Day and Leitch 2007;Garet et al 2001). Teachers report that professional learning opportunities that focus on subject matter (content learning), that involve 'hands-on' practice (active learning), and that are integrated into the daily life and priorities of schools and classrooms (coherent learning) are more likely to enhance teachers' knowledge and skills (Day and Leitch 2007;Garet et al 2001;Loxley et al 2007).…”
Section: Effective Professional Learningmentioning
confidence: 99%